Application of high resolution DLP stereolithography for fabrication of tricalcium phosphate scaffolds for bone regeneration. (19th June 2019) - Schmidleithner, Christina; Malferrari, Sara; Palgrave, Robert; Bomze, Daniel; Schwentenwein, Martin; Kalaskar, Deepak M
Abstract: Bone regeneration requires porous and mechanically stable scaffolds to support tissue integration and angiogenesis, which is essential for bone tissue regeneration. With the advent of additive manufacturing processes, production of complex porous architectures has become feasible. However, a balance has to be sorted between the porous architecture and mechanical stability, which facilitates bone regeneration for load bearing applications. The current study evaluates the use of high resolution digital light processing (DLP) -based additive manufacturing to produce complex but mechanical stable scaffolds based on β -tricalcium phosphate ( β -TCP) for bone regeneration. Four different geometries: a rectilinear Grid, a hexagonal Kagome, a Schwarz primitive, and a hollow Schwarz architecture are designed with 400 μ m pores and 75 or 50 vol% porosity. However, after initial screening for design stability and mechanical properties, only the rectilinear Grid structure, and the hexagonal Kagome structure are found to be reproducible and showed higher mechanical properties. Micro computed tomography ( μ -CT) analysis shows <2 vol% error in porosity and <6% relative deviation of average pore sizes for the Grid structures. At 50 vol% porosity, this architecture also has the highest compressive strength of 44.7 MPa (Weibull modulus is 5.28), while bulk specimens reach 235 ± 37 MPa. To evaluate suitability of 3D scaffolds produced by DLP methods for bone regeneration, scaffolds were cultured with murine preosteoblastic MC3T3-E1 cells. Short term study showed cell growth over 14 d, with more than two-fold increase of alkaline phosphatase (ALP) activity compared to cells on 2D tissue culture plastic. Collagen deposition was increased by a factor of 1.5–2 when compared to the 2D controls. This confirms retention of biocompatible and osteo-inductive properties of β -TCP following the DLP process. This study has implications for designing of the high resolution porous scaffolds for bone regenerative applications and contributes to understanding of DLP based additive manufacturing process for medical applications.